KINERJA SISTEM INFORMASI AKUNTANSI (SIA) PADA LEMBAGA PERKREDITAN DESA (LPD) DI KOTA DENPASAR - I Gusti Ayu Ratih Permata Dewi; Putu Diah Putri Idawati (KRISNA: Kumpulan Riset Akuntansi, 2021)
This study aimsa to determine the aeffect of training, task complexity, user involvement and human resource acapabilities on athe performance of the accounting information system at credit institutions in the city of Denpasar. The data used are primary data in the form of a questionnaire. The apopulation of this astudy were all LPD employees in Denpasar City with 214 employees using the accounting information system. The sampling technique in this study was purposive sampling. Therefore, a sample of 105 respondents who met the criteria was obtained. The test results show that training has no effect on the performance of the accounting information system at credit institutions in the city of Denpasar, while User Involvement, HR Capabilities have an effect on the performance of the Accounting Information System (SIA) at credit institutions in the city of Denpasar.